Factors management for workplace safety compliance in fossil power generation: comparison between assessed worldwide and Moroccan fossil fuel power plants - Younes El Bouti, Mohamed; Allouch, Mohamed (International Journal of Engineering and Technology, 2018)
Majority of workplace incidents are attributed to unsafe behavior. Despite all the implemented control measures, accidents still reoccur in the energy industry. Thus, the primary objective of this study is to identify the influencing factors on the employees’ behavioral safety compliance in Moroccan and worldwide Fossil Power Generation. The study analyses safety behavior and highlights the change trend by identifying the influencing factors on workers Safety-Related Behavior (S-RB). Therefore, the data were collected through the survey questionnaires of a five-point Likert scale, which have been dealing out to safety practitioners of sixteen Fossil Fuel Power Plants (FFPPs) that are located across nine countries. The inter-items consistency and reliability were measured by using Statistical Package for the Social Sciences (SPSS version 20) software. Besides, countermeasures were part of the survey. The study illustrates that the job factors are the most influencing of all other analyzed factors on workplace safety performance through their direct effects on workers S-RB, particularly the Workload which was revealed as the major affecting factor on S-RB in all the assessed 16 power plants (PPs). Furthermore, Worker Cooperation/Involvement and Training were found as the most common selected countermeasures in both conducted analyses (Worldwide and Moroccan PPs) in order to tackle effectively the identified influencing factors and reduce PPs accidents and critical safety behavior that contributes to injuries and losses.
Keywords: Countermeasures; Fossil Fuel Power Plants; Influencing Factors; Safety-Related Behavior.